2023
DOI: 10.1097/01.nurse.0000902968.61284.1e
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness techniques for clinical nurses

Abstract: The COVID-19 pandemic has heightened nurses' stress levels and made it even more challenging to carve time for self-care. This nurse, with over 14 years of experience in high-stress EDs and ICUs, shares mindfulness techniques to help nurses manage stress, reframe overwhelming situations, and improve their well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…Studies show that the program has various positive effects on nurses. Mindfulness is one strategy that nurses can be used to manage stress levels, reframe potentially overwhelming situations, and improve well-being (Sulosaari et al, 2022;Mancarella, 2023). A study by Duarte and Pinto-Gouveia (2016) found that mindfulness-based intervention in oncology nurses was effective in reducing burnout, compassion fatigue, and stress, and improving overall well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that the program has various positive effects on nurses. Mindfulness is one strategy that nurses can be used to manage stress levels, reframe potentially overwhelming situations, and improve well-being (Sulosaari et al, 2022;Mancarella, 2023). A study by Duarte and Pinto-Gouveia (2016) found that mindfulness-based intervention in oncology nurses was effective in reducing burnout, compassion fatigue, and stress, and improving overall well-being.…”
Section: Discussionmentioning
confidence: 99%
“…It is seen that although the work stress of the nurses is high, they do not use an appropriate stress management (Jordan et al 2016). In addition, studies indicate that the stress and burnout experienced by nurses negatively affect the quality of health care, patient safety, and satisfaction (Smith, 2014;Jordan et al, 2016;Mancarella, 2023). Healthy nurses and a healthy working environment increase the workforce, increase employee satisfaction, and increase retention of nurses and increase health care quality and patient satisfaction.…”
Section: Stress Management In Nursesmentioning
confidence: 99%